Comparison of Road Traffic Noise near High, Medium and Low Density Residential Areas in Nibong Tebal and Juru, Penang - Halim, Herni (International Journal of Integrated Engineering, 2019)
Nowadays, environmental noise pollution is ranked second among other environmental pollutions in terms of public health impacts due to rapid urbanization and growing traffic especially road traffic. The aim of this study is to assess traffic noise levels between different types of residential areas in Nibong Tebal and Juru, Penang. This study compares road traffic noise levels in high density (Juru) and medium density (Nibong Tebal) residential areas in Penang. The noise levels measurements were carried out periodically in the morning (from 0700 to 1100), evening (from 1600 to 1900), and at night (from 2200 to 2300) for 15 minutes using sound level meter. The traffic characteristics were measured simultaneously during noise levels measurements. One-Way Analysis of Variance (ANOVA) was used to determine any significant differences between two or more noise levels measured at sites of the study. Independent samples t-test was used to compare independent groups (noise levels at two different study sites and areas). In the present study, p values of less than 5% (p